RESTORATIVE JUSTICE ON BLASPHEMY CASES: OVERVIEW OF THE PROSECUTORS ROLE AND LEGAL REFORM - Rd. Muhammad Ikhsan; Hamonangan Albariansyah; Neisa Ang rum Adisti; Henny Yuningsih; Desia Rakhma Banjarani (Bengkoelen Justice : Jurnal Ilmu Hukum, 2024)
The absence of a clear definition and limitation of blasphemy can threaten justice in law enforcement in Indonesia. This has an impact on the process of resolving the blasphemy cases. Thus, the settlement of the penal or the courts in the settlement of blasphemy cases is considered ineffective. Based on that background, the problems that will be raised in this research are: How is the criminal law reform related to blasphemy in Indonesia based on the concept of restorative justice? How can the Prosecutor's Office play a role in the reformulation of blasphemy based on the concept of restorative justice? This study uses a descriptive normative research method with a qualitative approach. The research approach used is the statutory approach.The results of the study show that law enforcement in blasphemy tends to lead to pros and cons. This is due to problems with the regulation of blasphemy in Indonesia. There is no concrete definition of blasphemy and limitation on blasphemy in various laws in Indonesia. Therefore, there is a need for reformulation of blasphemy in Indonesia, one of which is through non-penal ways based on the concept of restorative justice by Law Enforcement Officials in Indonesia, one of which is the Prosecutor's Office. The reformulation is by: reforming legal regulations and provisions in the National Criminal Code and Draft of Criminal Procedure (RKUHAP); reformulation of administrative sanctions; and reformulation through penal mediation. Keywords: Blasphemy, Prosecutor's Office, Restorative Justice.